217k views
0 votes
Which are steps that could be used to solve 0 = 9(x2 + 6x) – 18 by completing the square? Check all that apply. 18 + 81 = 9(x2 + 6x + 9) 18 + 9 = 9(x2 + 6x + 9) 18 + 36 = 9(x2 + 6x + 36) 11 = (x + 3)2 StartRoot 342 EndRoot = (x + 6)2 StartRoot 99 EndRoot = (x + 3)2

2 Answers

2 votes

Answer:

18 + 81 = 9(x² + 6x + 9)

11 = (x + 3)²

When we are completing the square, we are going to move the value of c across the equals. We will do that by adding, and end up with

18=9(x²+6x)

We take the value of b (the coefficient of x), divide it by 2 and square it:

(6/2)²=3²=9

This is the value that completes the square. However, since the entire square is multiplied by 9, this value must be multiplied by 9 before we can add it across the equals:

18+9(9) = 9(x²+6x+9)

18+81=9(x²+6x+9)

99=9(x²+6x+9)

Dividing both sides by 9, we have:

11=x²+6x+9

11=(x+3)²

User Olaf Hess
by
5.0k points
2 votes

Answer:

18 + 81 = 9(x2 + 6x + 9) and 11 = (x + 3)2

Explanation:

EDG

User Mad
by
5.7k points